MiR-30c-5p regulates adventitial progenitor cells differentiation to vascular smooth muscle cells through targeting OPG - Zhang, Qing; Chen, Ting; Zhang, Yun; Lyu, Lingxia; Zhang, Bohuan; Huang, Chengchen; Zhou, Xuhao; Wu, Yutao; Li, Zhoubin (Stem cell research & therapy, 2021)
Background As the most important component of the vascular wall, vascular smooth muscle cells (VSMCs) participate in the pathological process by phenotype transformation or differentiation from stem/progenitor cells. The main purpose of this study was to reveal the role and related molecular mechanism of microRNA-30c-5p (miR-30c-5p) in VSMC differentiation from adventitial progenitor cells expressing stem cell antigen-1(Sca-1). Methods In this study, we detected the expression of miR-30c-5p in human normal peripheral arteries and atherosclerotic arteries. In vitro, a stable differentiation model from adventitial Sca-1 + progenitor cells to VSMCs was established using transforming growth factor-β1 (TGF-β1) induction and the expression of miR-30c-5p during the process was observed. Then, we explored the effect of miR-30c-5p overexpression and inhibition on the differentiation from adventitial Sca-1 + progenitor cells to VSMCs. The target genes of miR-30c-5p were identified by protein chip and biological analyses and the expression of these genes in the differentiation process were detected. Further, the relationship between the target gene and miR-30c-5p and its effect on differentiation were evaluated. Finally, the co-transfection of miR-30c-5p inhibitor and small interfering RNA (siRNA) of the target gene was implemented to verify the functional target gene of miR-30c-5p during the differentiation from adventitial Sca-1 + progenitor cells to VSMCs, and the dual-luciferase reporter gene assay was performed to detect whether the mRNA 3′untranslated region (UTR) of the target gene is the direct binding site of miR-30c-5p. Results The expression of miR-30c-5p in the human atherosclerotic arteries was significantly lower than that in the normal arteries. During the differentiation from adventitial Sca-1 + progenitor cells to VSMCs, the expression of VSMC special markers including smooth muscle α-actin (SMαA), smooth muscle-22α (SM22α), smooth muscle myosin heavy chain (SMMHC), and h1-caponin increased accompanied with cell morphology changing from elliptic to fusiform. Meanwhile, the expression of miR-30c-5p decreased significantly. In functional experiments, overexpression of miR-30c-5p inhibited SMαA, SM22α, SMMHC, and h1-caponin at the mRNA and protein levels. In contrast, inhibition of miR-30c-5p promoted the expression of SMαA, SM22α, SMMHC, and h1-caponin. The target gene, osteoprotegerin (OPG), was predicted through protein chip and bioinformatics analyses. Overexpression of miR-30c-5p inhibited OPG expression while inhibition of miR-30c-5p had an opposite effect. Co-transfection experiments showed that low expression of OPG could weaken the promotion effect of miR-30c-5p inhibitor on the differentiation from adventitial Sca-1 + progenitor cells to VSMCs and the dual-luciferase reporter gene assay demonstrated that miR-30c-5p could target the mRNA 3′UTR of OPG directly. Conclusions This study demonstrates that miR-30c-5p expression was significantly decreased in atherosclerotic arteries and miR-30c-5p inhibited VSMC differentiation from adventitial Sca-1 + progenitor cells through targeting OPG, which may provide a new target for the treatment of VSMCs-associated diseases.